Biomimetic, mussel-inspired surface modification of 3D-printed biodegradable polylactic acid scaffolds with nano-hydroxyapatite for bone tissue engineering - Chi, Minghan; Li, Na; Cui, Junkui; Karlin, Sabrina; Rohr, Nadja; Sharma, Neha; Thieringer, Florian M. (Frontiers in Bioengineering and Biotechnology, 2022)
Polylactic acid (PLA) has been widely used as filaments for material extrusion additive manufacturing (AM) to develop patient-specific scaffolds in bone tissue engineering. Hydroxyapatite (HA), a major component of natural bone, has been extensively recognized as an osteoconductive biomolecule. Here, inspired by the mussel-adhesive phenomenon, in this study, polydopamine (PDA) coating was applied to the surface of 3D printed PLA scaffolds (PLA@PDA), acting as a versatile adhesive platform for immobilizing HA nanoparticles (nHA). Comprehensive analyses were performed to understand the physicochemical properties of the 3D-printed PLA scaffold functionalized with nHA and PDA for their potent clinical application as a bone regenerative substitute. Scanning electron microscopy (SEM) and element dispersive X-ray (EDX) confirmed a successful loading of nHA particles on the surface of PLA@PDA after 3 and 7 days of coating (PLA@PDA-HA3 and PLA@PDA-HA7), while the surface micromorphology and porosity remain unchanged after surface modification. The thermogravimetric analysis (TGA) showed that 7.7 % and 12.3 % mass ratio of nHA were loaded on the PLA scaffold surface, respectively. The wettability test indicated that the hydrophilicity of nHA-coated scaffolds was greatly enhanced, while the mechanical properties remained uncompromised. The 3D laser scanning confocal microscope (3DLS) images revealed that the surface roughness was significantly increased, reaching Sa (arithmetic mean height) of 0.402 μm in PLA@PDA-HA7. Twenty-eight days of in-vitro degradation results showed that the introduction of nHA to the PLA surface enhances its degradation properties, as evidenced by the SEM images and weight loss test. Furthermore, a sustainable release of Ca2+ from PLA@PDA-HA3 and PLA@PDA-HA7 was recorded, during the degradation process. In contrast, the released hydroxyl group of nHA tends to neutralize the local acidic environments, which was more conducive to osteoblastic differentiation and extracellular mineralization. Taken together, this facile surface modification provides 3D printed PLA scaffolds with effective bone regenerative properties by depositing Ca2+ contents, improving surface hydrophilicity, and enhancing the in-vitro degradation rate.